Temporary Tattoo Decorations on the Body from the Perspective of Islamic Jurisprudence - Musriwan, Musriwan; Andi Dahmayanti; Andi Indra Putri; Risdayani, Risdayani; Nur Utami (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to examine in depth the law of using temporary tattoos in the perspective of Islamic fiqh. The research method used in this study is library research with a phenomenological and normative approach. The data were collected through documentation methods and subsequently analyzed using qualitative analysis. The results of this study indicate that the law of using temporary tattoo decoration on the body in the perspective of Islamic fiqh is still in dispute (khilāfiyyah). Some contemporary scholars allow temporary tattoos on the condition that they do not contain images of animate beings, do not resemble non-Islamic culture, do not block the water of ablution, and are not permanent. However, some conservative scholars reject the use of temporary tattoos on the grounds of prudence (wara') and the application of the sad al-Zara'i rule to prevent greater harm, such as the possibility of resembling non-Muslim practices and obstruction of wudu. Therefore, the use of temporary tattoos should be considered based on intention, materials, cultural context, and its impact on worship obligations. This study recommends a wise and selective attitude in the use of temporary tattoos in accordance with the principles of Islamic law. This research is expected to make a significant contribution to the understanding of fiqh law related to the use of temporary tattoos and can be a practical guide for muslim communities as well as a valuable reference for further research.